FEAR ITSELF : AVENGERS - Bendis, Brian Michael; Brevoort, Tom (New York, NY : Marvel Worldwide, Inc., 2011)
The Red Skull's daughter has unleashed an evil as old as Midgard itself: The Serpent has risen to reclaim Earth, recruiting seven of its most powerful superhumans as his advance guard, the Worthy. The result is all-out action in classic Avengers style! The Thing vs. Red Hulk! Spider-Woman vs. Hulk! Steve Rogers vs. Master Man! And Squirrel Girl vs. the Red Skull's Nazi hordes?! Plus: What happens when Daredevil, the Man Without Fear, stands up to fear itself?.
NEW AVENGERS #14-16 / ARTIST MIKE DEODATO ; COLORIST RAIN BEREDO ; LETTERER VC'S JOE CARAMAGNA
"Contains material originally published in magazine form as Avengers #13-17 and New Avengers #14-16"--Title page verso.
Keywords: Avengers (Fictitious characters) -- Comic books, strips, etc; Comic books, strips, etc. -- United State